Improved chamfer matching method for surface mount component positioning. Issue 12 (10th October 2017) - Bai, Lifei; Yang, Xianqiang; Gao, Huijun
Abstract : This study is concerned with the surface mount component positioning problem and an improved chamfer matching method based on iterative position and rotation angle estimation approach is proposed. Instead of performing matching of the image with different pre‐specified angle templates pixel by pixel, as does in traditional chamfer matching methods, the gradient information of the distance transform image is incorporated into the chamfer matching method and reduced computational cost of the method is achieved. The iterative formulas to update the translation and rotation angle are derived by reference to the characteristic of rigid body motion. The criterions of search region establishment, seed point selection and terminal conditions are given. The effectiveness of the proposed method is verified by applying the method to component positioning with actual captured images.